Vocabulary recommendation approach for forced migrants using informal language learning tools - Abou-Khalil, Victoria; Helou, Samar; Chen, Mei‐Rong Alice; Flanagan, Brendan; Lecailliez, Louis; Pinkwart, Niels; Ogata, Hiroaki (Universal access in the information society, 2022)
Learning a new language is a major challenge faced by many forced migrants. Current vocabulary learning curricula are not adapted to the migrants’ needs, which makes the learning process even more challenging. Today, the widespread use of smartphones among forced migrants provides us with new opportunities to collect and recommend the vocabulary they need. In this work, we propose a demographic- and content-based vocabulary recommendation approach that considers the migrant’s status, migration stage, and vocabulary themes. Based on our approach, the vocabulary recommended to a forced migrant belongs to the same theme as the vocabulary that other forced migrants in the same migration stage chose to learn. The approach was evaluated with 37 Syrian refugees in Lebanon and Germany that used SCROLL, an informal language learning tool, to learn their target language. We compared the learning achievement and motivation of the participants when they learned the recommended vocabulary and the standard textbook vocabulary. Our results showed that the proposed vocabulary recommendation approach resulted in higher learning achievement for refugees in Germany and higher motivation levels for refugees in Germany and Lebanon. Tailored vocabulary recommendation approaches showed potential to improve the language learning experience of forced migrants and warrant further study.